INTERACTION BETWEEN MEMBER STATES OF THE COOPERATION COUNCIL OF TURKIC SPEAKING STATES IN THE FIELD OF HEALTH CARE AND ALTERNATIVE ENERGY - Shodikulov Eldor Sherzodovich (Western European Studies, 2025)
This article reflects the recent cooperation of the Cooperation Council of TurkicSpeaking States in Central Asia, the agreements of the states in various fields, especially in the economic and political spheres. This working platform, established within the framework of the Organization of Turkic States, aims to ensure regional cooperation by coordinating the policies of the member states, strengthening the management of energy resources and the health sector through the Center for Strategic Studies.
Keywords: Strategic research; cooperation; Health